Eksistensi Teh Nyaneut Sebagai Tradisi Warisan Leluhur Budaya Sunda - Bagus syah putra (Studi Budaya Nusantara, 2022)
The tradition of drinking Nyaneut Tea is a culture that has been passed down from generation to generation and is often used as a guide for Sundanese people to respect and stay in touch through serving a cup of warm tea. The culture of the Nyaneut Tea tradition is slowly fading among the people with low awareness of preservation, wealth, and culture and the lack of existence of the Nyaneut Tea Tradition so that tea is only seen as a side dish and without meaning. This study aims to determine the existence of the Nyaneut Tea Tradition today, the efforts of the local community to maintain the Nyaneut Tea Tradition and the background of the Nyaneut Tea occurrence so that it can become an ancestral cultural heritage that lasts from generation to generation. This study uses descriptive qualitative methods, to obtain strong data by conducting interviews, observations, and documentation. The location determination was carried out in Cigedug village, Garut Regency as a place for research activities. The results of the study show that the Nyaneut Tea Tradition is indeed lacking in existence among today's society. Nyaneut culture has begun to fade even though Nyaneut itself has many benefits for body health and teaches the rules of drinking tea that need to be applied to the community for etiquette.